Faktor Pendidikan, Status Perkawinan dan Jumlah Tanggungan serta Dampaknya pada Keaktifan Perempuan Mengikuti Kelompok Arisan (Survei Kelompok Arisan Ibu Rumah Tangga dan Profesi) - novita, novita (Jurnal Daya Saing, 2017)
Abstract: Learning the problems faced by women in the concept of women empowerment makes it important to always get a solution. Women's arisan groups become one of the place of empowerment for women to grow and develop in order to increase prosperity and equality. The issue of women's activeness in arisan groups is one of the problems that causes less successful empowerment to be implemented. Through survey methods conducted on housewives and professional groups who joined as members in arisan groups in Pekanbaru City by using questionnaires distributed to 31 members of the arisan group taken proportionally and analyzed by using multiple regression analysis and assisted with the program WarpPLS. The result of the research shows that education factor, status and amenability factor give significant influence to women activity in arisan group (P-value: 0,02, 0,03 and 0,01). Educational and status factors have a negative influence on liveliness and amenability factors have a positive effect. 26% of women's activeness in the arisan group can be explained through education factor, status and amenability. Keywords: Education, Marital Status, Amenability and Activity of Women